STRATEGI MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XII AP 1 SMK NEGERI 5 DENPASAR SELAMA PEMBELAJARAN DARING DENGAN APLIKASI GOOGLE CLASSROOM - I Kadek Arta Jaya; Ni Wayan Arsini (Guna Widya: Jurnal Pendidikan Hindu, 2023)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. Learning is part of the element that has a very dominant role to realize the quality of both the process and the education graduates (outputs). Learning also has an influence that causes the quality of education to be low. This means that learning is very dependent on the ability of teachers to implement or package the learning process. Learning that is carried out properly and appropriately will make a very dominant contribution to students, otherwise learning that is carried out in a bad way will make it difficult for the potential of students to be developed or empowered. Based on this background, a class action research was conducted which aims to determine the improvement in learning outcomes of class XII AP1 students at SMK Negeri 5 Denpasar by utilizing the Google Classroom application as one of the learning strategies during the COVID-19 pandemic in the historical material on the development of Hindu religious culture. in Asia. This research is a classroom action research which was carried out for two cycles. Each cycle consists of stages of planning (planning), action (action), observation (observation), and reflection (reflection). The learning strategy used is by utilizing the Google Classroom application. The advantage of this application is that it can make it easier for teachers to manage learning and convey information precisely and accurately to students. Based on the results of the discussion and analysis during the research, the results have shown that learning strategies by utilizing technology in the form of the Google Classroom application during the Covid-19 pandemic can improve student learning outcomes in the historical material of the development of Hindu religious culture in Asia class XII AP1 SMK Negeri 5 Denpasar. as evidenced by the test results at the end of the first cycle there were 6 students with a percentage of completeness of 18% and an increase in the percentage of completeness in the second cycle of 94% of 31 students. Based on these results, it can be stated that the target percentage of students' completeness has exceeded the minimum limit value.